Psychological distance between family members and its influence on the teenager’s personality - Zemsh, Marina B.; Starodumov, Leonid L.; Ignatova, Ekaterina S.; Lazareva, Yuliya B.; Dubrovin, Alexsei K. (Opción, 2019)
The purpose of the study is to study the influence of the psychological distance between family members on the formation of the personality of a teenager. Statistical methods were used to construct a linear dependence of the average academic performance of a teenager on the shortest distance of his relationship with a relative. As a result, close relationships in the family are an important factor supporting teenagers in their studies. In conclusion, improve the relationship in the family, it is advisable to combine psycho-correctional work with teenagers in training with psychological and pedagogical work with their parents (guardians).